Analysis of the Utilization of Village Fund Allocation (ADD) in Botto Village Pitu Riase District Sidenreng Rappang Regency - Muhammad Nurul Fikri; Adinda Aulia Salsabila; Jasmiati; Arfianty; Sariana Damis (www.amertainstitute.com, 2023)
The allocation of village funds is one of the government policies that is prioritized to finance development and community empowerment whose implementation is prioritized by self management using local resources, and is strived to absorb more local community workers. his study aims to determine themanagement and utilization of village fund allocations (ADD) in Botto Village, Pitu Riase District, Sidenreng Rappang Regency using an empirical juridical qualitative approach. The data collection techniques used in this study are observation, interviews, and documentation. The results of this study indicate that, the management of village fund allocations which are determined based on the amount of Village Fund Allocation received by each village in Sidenreng Rappang Regency, especially Botto village runs according to the rules of the city government and the rules in Law Number 6 of 2014 concerning Villages and is implemented properly. Seeing the many developments that have been realized and followingthe mechanism in managing the allocation of funds and the utilization of village fund allocations in development, it is well realized and can be felt by various ranks, especially the village community itself as well as in improving the economic level of the community in Botto Village, Pitu Riase District, Sidenreng Rappang Regency. changes in accordance with community expectations, supervision of Botto Village has been said to be able to carry it out, the utilization of village fund allocations in development is well realizedand can be felt by various ranks, especially the village community itself as a whole. so as to improve the economic standard of the community.